Monitoring of Acute Chagas Disease cases in Brazil: a descriptive study (Research, Society and Development, 2022)
Introduction: Although identified more than 100 years ago, Chagas Disease remains uncontrolled in Brazil, both due to the unstable number of cases and the lack of effective public policies to combat it. In a recent context, the monitoring of this and other neglected tropical diseases may have lost quality due to the arrival of new acute diseases in the country and the resulting work overload in health care and attention services. Objective: to evaluate the epidemiological profile of ACD by comparing the historical series available in the Notifiable Diseases Information System (SINAN), tabulated between 2011 and 2020. Method: Public data from the Notifiable Diseases Information System collected by the System were used Single Health. Results: Applied the quantitative techniques of descriptive epidemiology, it is suggested that, in endemic and highly vulnerable areas for the disease, COVID-19 may have contributed to the worsening of underreporting of Chagas, which showed a reduction close to 50% compared to to the average of previous years. Conclusion: Assuming that at this moment the eradication of Chagas Disease and COVID-19 do not seem close, the strengthening of Health Surveillance is a critical success factor for the construction of more favorable health scenarios.